MANAGEMENT OF INTERNATIONAL PORTFOLIO FINANCIAL - Gomero Gonzales, Nicko Alberto (2009)
If financial markets are volatilized, the traders have to evaluate new alternatives to place their capital at risk. In the Euro Area, Asia and North America, stock markets are developed which provide the opportunity to demand equity securities of major global corporations on the planet, like Chevron, Walt Disney, Telephonic, Yahoo, Mac Donald’s. As financial manuals say, the best strategy to minimize risks for investment of this nature, is structuring a well diversified portfolio, in light of this theory then, would need to hedge or speculative investors, whether institutional or retail, management titles global stock markets, which as you know are represented by the Hang Seng, FTSE, Nasdaq, Dow Jones, Bobespa, among others, only then will be in an advantageous position to counter the shocks stemming from economic cycles.